A quasistatic unilateral contact problem with friction for nonlinear elastic materials - Touzaline, Arezki; Teniou, Djamel Eddine (Mathematical Modelling and Analysis, 2007)
The aim of this paper is to prove the existence of a solution to the quasistatic unilateral contact problem with a modified version of Coulomb’s law of dry friction for nonlinear elastic materials. We derive a variational incremental problem which admits a solution if the friction coefficient is sufficiently small and then by passing to the limit with respect to time we obtain the existence of a solution. First Published Online: 14 Oct 2010